Latest beam test results from RICH prototypes using hybrid photo detectors and multi anode PMTs - Albrecht, E; Alemi, M; Barber, G; Bibby, J; Brook, N; Duane, A; Easo, S; Eklund, L; Gibson, V; Gys, T; Halley, A; Harnew, N; et al. (1999)
Beam tests were performed in 1998 to investigate the performance of a prototype of the downstream RICH of the LHCb using hybrid photo-diodes and multi anode PMTs. The angular resolutions obtained from these photodetectors under various experimental configurations are compared with the expectations from simulation. (C) 1999 Elsevier Science B.V. All rights reserved.